New biomarkers for differentiating renal neoplasms with eosinophilic cytoplasm: DARS2, reelin, and enkurin : Protein markers for differential diagnosis of renal neoplasms - Balta, Hilal; Kocaman, Nevin; Ucer, Ozlem (Journal of Surgery and Medicine, 2023)
Background/Aim: Chromophobe renal cell carcinoma (CRCC), eosinophilic variant clear cell RCC, and oncocytomas are renal neoplasms with eosinophilic cytoplasm, and their differential diagnosis is challenging despite significant advances in molecular pathology. Although many biomarkers have been identified for the differential diagnosis of these neoplasms, specific markers have not yet been reported. No studies were found in the literature on the relationship between these tumors and the new molecules DARS2, reelin, and enkurin. This paper aims to determine the roles of these proteins in renal neoplasms with eosinophilic cytoplasm. Methods: The study retrospectively analyzed 30 EC RCC, 30 CRCC, and 30 oncocytoma cases, evaluated among renal neoplasms with eosinophilic cytoplasm, independent of demographic characteristics, in the Fırat University Medical Pathology Laboratory between 2012 and 2022. The most representative samples of the tumor were selected for each group, and the expression of DARS2, reelin, and enkurin proteins was evaluated by the immunohistochemical method. Results: The histoscore of DARS2 expression was highest in EC RCC and least in CRCC. DARS2 was seen to differentiate CRCC from oncocytoma and EC RCC. The histoscore of reelin and enkurin protein expression was highest in oncocytoma and lowest in ECRCC. The difference between the groups was statistically significant (P<0.05). Conclusion: DARS2 can be a useful biomarker for differentiating CRCC from EC RCC and oncocytoma, and enkurin and reelin can differentiate among these three groups.